2011
DOI: 10.1111/j.1467-8330.2011.00861.x
|View full text |Cite
|
Sign up to set email alerts
|

Community Volunteering as Neoliberal Strategy? Green Space Production in Berlin

Abstract: The task for critical urban research is to analyze processes of neoliberalization "on the ground". This paper examines-based on original empirical research-in how far the outsourcing of former local state responsibilities for public services and urban infrastructure is expressed in the promotion of community gardening in Berlin (Germany). It shows the contradictory outcomes: on the one hand, a failing strategy of outsourcing towards residents and the opening up of opportunity structures for other interests. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
196
0
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(205 citation statements)
references
References 65 publications
0
196
0
9
Order By: Relevance
“…The majority of the research on such activity, however, has been of a qualitative nature and has adopted a largely conceptual stance in its appreciation of the emergence and impact of such approaches. For example, ethnographic studies investigating the views and goals of participants in social-ecological actor groups have succeeded in elucidating the motives which drive such engagement (Glover, 2004;Glover et al, 2005;Jones, 2005;Kingsley et al, 2009;Corrigan, 2011;Rosol, 2012;Green and Phillips, 2013). These studies have unpicked the genesis and organisational structure of collaborative groups involved in environmental stewardship and the importance of social-ecological networks at various levels of agency has been highlighted and promoted (Andersson, 2007;Ernstson et al, 2008;Biggs et al, 2010).…”
Section: Social-ecological Innovation In Urban Areasmentioning
confidence: 99%
“…The majority of the research on such activity, however, has been of a qualitative nature and has adopted a largely conceptual stance in its appreciation of the emergence and impact of such approaches. For example, ethnographic studies investigating the views and goals of participants in social-ecological actor groups have succeeded in elucidating the motives which drive such engagement (Glover, 2004;Glover et al, 2005;Jones, 2005;Kingsley et al, 2009;Corrigan, 2011;Rosol, 2012;Green and Phillips, 2013). These studies have unpicked the genesis and organisational structure of collaborative groups involved in environmental stewardship and the importance of social-ecological networks at various levels of agency has been highlighted and promoted (Andersson, 2007;Ernstson et al, 2008;Biggs et al, 2010).…”
Section: Social-ecological Innovation In Urban Areasmentioning
confidence: 99%
“…The paper proposes a definition of affect that stems from a Spinozist lineage emphasising feeling, relationality and capacity and deploys affect not in ontological terms but as a phenomenological register of embodied connections that shape and are shaped by individual and collective subjectivities. 11 Wetherell (2015: 152) Mostafanezhad, 2012;Rosol, 2012;Dean, 2015). This re-orientates volunteering towards a logic of individual utility maximisation (albeit premised on social cooperation), thereby transforming the affective structures in which it occurs.…”
Section: Affect As Remuneration: Volunteeringmentioning
confidence: 99%
“…Despite the growing attention paid to the sharing economy and household food production, the non-market and non-monetized sharing of home-grown food has largely escaped scholars' attention [11]. There are several studies which revealed the multidimensional roles of non-market food provision through home-gardens and community gardens in developed countries [12][13][14][15][16]. However, the existing literature has not examined the relationship between such sharing practices and landscape characteristics.…”
Section: Introductionmentioning
confidence: 99%